Sonographic evaluation of fetal scrotum, testes and epididymis - Álvaro López Soto; Jose Luis Meseguer González; María Velasco Martínez; Rocío López Pérez; Inmaculada Martínez Rivero; Mónica Lorente Fernández; Olivia García Izquierdo; Juan Pedro Martínez Cendán (Korean Society of Obstetrics and Gynecology, 2021)
External male genitalia have rarely been evaluated on fetal ultrasound. Apart from visualization of the penis for fetal sex determination, there are no specific instructions or recommendations from scientific societies. This study aimed to review the current knowledge about prenatal diagnosis of the scrotum and internal structures, with discussion regarding technical aspects and clinical management. We conducted an article search in Medline, EMBASE, Scopus, Google Scholar, and Web of Science databases for studies in English or Spanish language that discussed prenatal scrotal pathologies. We identified 72 studies that met the inclusion criteria. Relevant data were grouped into sections of embryology, ultrasound, pathology, and prenatal diagnosis. The scrotum and internal structures show a wide range of pathologies, with varying degrees of prevalence and morbidity. Most of the reported cases have described incidental findings diagnosed via striking ultrasound signs. Studies discussing normative data or management are scarce.